Relationship between Self-Concept and Teacher Performance of State Madrasah Tsanawiyah in Pandeglang Regency - Anis Zohriah; Anis Fauzi; Fazrurrakhman Al Farisi; Euis Asyiah (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2025)
This study was motivated by the phenomenon of low teacher performance in the State Madrasah Tsanawiyah in Pandeglang, Banten. Self-concept is one of the factors influencing teachers' performance in State Madrasah Tsanawiyah in Pandeglang. This study aims to analyze the relationship between self-concept and teachers' performance. The research method used is quantitative. This type of research is descriptive correlational. The study population comprised 267 teachers, and the sample comprised 56 teachers. The research instrument was a questionnaire prepared using a Likert-scale format. The data were analyzed using descriptive statistics and correlation analysis in SPSS 23.00. The results indicated that the teacher's self-concept was in the moderate range, suggesting a positive self-image. Teachers' performance is also in the moderate category, indicating that teachers already possess effective skills in their work to achieve good performance. A positive and significant relationship exists between self-concept and teacher performance at Tsanawiyah State Madrasah in Pandeglang Regency. This means that high- and low-performing teachers can be explained by self-concept, and that performing teachers will perform higher. The results of data analysis obtained R = 0.710 with degree p = 0.000 (p < 0.05), R2 = 50.5%. This study demonstrates a significant and positive increase in teachers' self-concept and performance at State Madrasah Tsanawiyah in Pandeglang Regency.